2008
DOI: 10.1002/hbm.20633
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks involved in artistic creativity

Abstract: Creativity has been proposed to be either the result of solely right hemisphere processes or of interhemispheric interactions. Little information is available, however, concerning the neuronal foundations of creativity. In this study, we introduced a new artistic task, designing a new tool (a pen), which let us quantitatively evaluate creativity by three indices of originality. These scores were analyzed in combination with brain activities measured by functional magnetic resonance imaging (fMRI). The results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
120
2
4

Year Published

2011
2011
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(137 citation statements)
references
References 82 publications
(117 reference statements)
11
120
2
4
Order By: Relevance
“…The right ACC may be associated with the detection of cognitive conflicts between old and new ideas during insight problem solving and resolution. The specific role of the bilateral PCC is not clear, but neuroimaging studies on creative thinking have shown that the right PCC is activated in novices operating a digit count task [37]. Neuroimaging studies on the neural correlates of economic and moral decision-making demonstrate that the bilateral PCC (especially the right PCC) is associated with the expected reward probability of expected economic utility [38], expected moral utility, practical moral utility, and event probabilities (primarily right PCC) [39].…”
Section: Cingulate Cortexmentioning
confidence: 99%
“…The right ACC may be associated with the detection of cognitive conflicts between old and new ideas during insight problem solving and resolution. The specific role of the bilateral PCC is not clear, but neuroimaging studies on creative thinking have shown that the right PCC is activated in novices operating a digit count task [37]. Neuroimaging studies on the neural correlates of economic and moral decision-making demonstrate that the bilateral PCC (especially the right PCC) is associated with the expected reward probability of expected economic utility [38], expected moral utility, practical moral utility, and event probabilities (primarily right PCC) [39].…”
Section: Cingulate Cortexmentioning
confidence: 99%
“…In a sense, the acquisition and subsequent training of a skill can be viewed as preceding and potentially modulating activity during both generation and revision [Wallas, 1926]. A few neuroimaging studies have explored differences between trained and untrained individuals during the generation phase, as subjects engaged in real [Berkowitz and Ansari, 2010] or imagined artistic tasks [Bhattacharya and Petsche, 2005; Fink et al, 2009; Kowatari et al, 2009]. Although all studies reported differences between experts and novices, the results are subtle and somewhat variable.…”
Section: Introductionmentioning
confidence: 99%
“…B. rechtsseitige präfrontale Aktivität mit semantischem divergenten Denken in Verbindung gebracht [49]. Zudem zeigt sich eine stärkere rechtsseitige präfrontale Aktivierung bei kreativen gegenüber weniger kreativen Probanden während der Bearbeitung von Kreativitätsaufgaben [12,54]. Aber auch linksseitige präfrontale Aktivität wird mit kreativen Kognitionen in Verbindung gebracht [5,32].…”
Section: Neurobiologie Der Kreativitätunclassified